Social Group Dynamics and Patterns of Latin American Integration Processes [Dinâmicas de Grupos Sociais E Processos de Integração Na América Latina] [Dinámicas de Grupos Sociales y Procesos de Integración en América Latina] - Dube, S (Universidad de los Andes, Bogota Colombia, 2017)
This article proposes to incorporate social psychology elements with mainstream political science and international relations theories to help understand the contradictions related to the integration processes in Latin America. Through a theoretical analysis, it contributes to the challenge proposed by Dabène (2009) to explain the “resilience” of the Latin American regional integration process in spite of its “instability and crises.” Our main proposition calls for considering Latin America as a community and its regional organizations as “social groups.” In conclusion, three phenomena from the field of social psychology and particularly social group dynamics shed light on these contradictory patterns: the value of the group and the emotional bond, groupthink, and cognitive dissonance. © 2017, Universidad de los Andes, Bogota Colombia. All rights reserved.